Integrin inhibition differentially remodels vascular networks in lung metastases driven by vessel co-option or angiogenesis - Laura Marcos-Zazo; Iván Carrera-Aguado; Jesús Gómez-Escudero; Patricia Berlana-Galán; Irene Torre-Cea; Elena Guerra-Paes; Celia Redondo-Gonzalez; Juan Sánchez-Mateos; Daniel Cáceres-Calle; Óscar Maiques; Miguel Pericacho; Susana Fraile; et al. (Angiogenesis, 2026)
Tumor progression depends on an adequate blood supply to sustain oxygen and nutrients delivery. While tumor angiogenesis involves the formation of new blood vessels from pre-existing ones, vessel co-option represents a non-angiogenic vascularization strategy whereby tumor cells utilize pre-existing host vessels. Co-opted vessels have been considered refractory to anti-angiogenic therapies, and pharmacological modulation of co-opted vessels remains limited. In this study, we investigate the effects of low-dose cilengitide on tumor vascular remodeling in vessel co-option and angiogenic metastatic models. Our results reveal that cilengitide exerts distinct vascular effects depending on the mode of tumor vascularization. In vessel co-option-driven tumors, cilengitide treatment is associated with the remodeling of the co-opted vasculature into a more organized normalized vascular network, characterized by an increased number of functional blood vessels and enhanced vascular barrier integrity. In contrast, in angiogenic-driven tumors, cilengitide treatment promotes an expansion of the vascular network consistent with augmented, but structurally immature angiogenesis. Importantly, vascular remodeling in vessel co-option metastases is accompanied by enhanced blood vessel perfusion and reduced hypoxia, which correlates with enhanced responsiveness to chemotherapy. Conversely, in angiogenic metastases, the vascular network induced by low-dose cilengitide fails to support immunocompetent microenvironmental features and is associated with increased chemotherapy resistance. This study provides the first evidence that co-opted vasculature can be therapeutically targeted via integrin inhibition, suggesting vascular normalization remodeling as a potential strategy to overcome resistance in tumors undergoing vessel co-option.